2008
DOI: 10.1088/0963-0252/17/3/035015
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure radio frequency glow discharges in argon: effects of external matching circuit parameters

Abstract: Numerical simulations of radio frequency atmospheric pressure argon glow discharges were performed using a one-dimensional hybrid model. The discharge simulations were carried out for a parallel plate electrode configuration with an inter-electrode gap of 1.0 mm together with an external matching circuit. The external matching circuit parameters were found to have significant effect on the discharge characteristics. The results indicate that the discharge can operate at either the α or γ mode depending on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 29 publications
(68 reference statements)
6
28
0
Order By: Relevance
“…This modeling approach can be justified by the following reasons. In the present work, the voltage drops in the sheath regions close to the electrode surfaces are estimated by simulations at the same conditions but with homogeneous compositions [28,29]. The simulation shows that the electrical field (E = 7500 V/cm) in the bulk plasma region is nearly constant at different conditions as far as the applied voltage is constant, which was confirmed during the experiments.…”
Section: Kinetic Modeling Of Plasma-flame Interactionsupporting
confidence: 68%
“…This modeling approach can be justified by the following reasons. In the present work, the voltage drops in the sheath regions close to the electrode surfaces are estimated by simulations at the same conditions but with homogeneous compositions [28,29]. The simulation shows that the electrical field (E = 7500 V/cm) in the bulk plasma region is nearly constant at different conditions as far as the applied voltage is constant, which was confirmed during the experiments.…”
Section: Kinetic Modeling Of Plasma-flame Interactionsupporting
confidence: 68%
“…This is because the quenching rate of O * by O 2 is several orders of magnitude higher than that by He and therefore at high oxygen concentrations (> 5 000 ppm) the density of O * starts to decrease, while the density of O still increases. Although O( 5 P) and O( 3 P) are not explicitly considered in the global model, a similar trend to that of O * should be expected as their quenching rate by O 2 molecules is two orders of magnitude larger than the quenching rate by He atoms (≈7 × 10 − 10 s − 1 by O 2 vs. 7 × 10 − 12 s − 1 by He) 52, 53…”
Section: Source Of Reactive Oxygen Species (Ros)mentioning
confidence: 67%
“…The significance of the Penning excitation by metastable Ar was already demonstrated in a previous work [167], which showed that a noticeable continuum emission occurred when H 2 was added to the argon discharge but not when added to the neon discharge. Moreover, most numerical simulation results show that the metastable Ar density is an order of magnitude larger than the electron density [34,168].…”
Section: Hydrogen Molecule (H 2 )mentioning
confidence: 99%